Benefits and challenges of a personal budget for people with mental health conditions or intellectual disability: A systematic review - Micai, Martina; Gila, Letizia; Caruso, Angela; Fulceri, Francesca; Fontecedro, Elisa; Castelpietra, Giulio; Romano, Giovanna; Ferri, Mila; Scattoni, Maria Luisa (Frontiers in Psychiatry, 2022)
Personal budgets (PBs) may improve the lives of people with mental health conditions and people with intellectual disability (ID). However, a clear definition of PB, benefits, and challenges are still faded. This work aims to systematically review evidence on PBs use in mental health and ID contexts, from both a qualitative and quantitative perspective, and summarize the recent research on interventions, outcomes, and cost-effectiveness of PBs in beneficiaries with mental health conditions and/or ID. The present systematic review is an update of the existing literature analyzed since 2013. We performed a systematic search strategy of articles using the bibliographic databases PubMed and PsycINFO. Six blinded authors screened the works for inclusion/exclusion criteria and two blinded authors extracted the data. We performed a formal narrative synthesis of the findings from the selected works. 9,800 publications were screened and 29 were included. Improvement in responsibility and awareness, quality of life, independent living, paid work, clinical, psychological, and social domains, and everyday aspects of the users’ and their carers’ life have been observed in people with mental health conditions and/or ID. However, the PBs need to be less stressful and burdensome in their management for users, carers, and professionals. In addition, more quantitative research is needed to inform PBs' policymakers.